Fabricación y acondicionamiento de módulo didáctico para ensayos de impacto - Lozano Villanueva, Glider Darwin (2018)
In the materials used in the construction, different properties are manifested when subjected to external stresses. To determine the mechanical properties of the materials, different mechanical testing machines are used, with the Charpy test we can establish exclusively the impact resistance, tenacity, in many cases when not taking into account these factors, great damage has been produced. The present project aims to show the different stages of the manufacturing process of the didactic impact test machine, as well as: know the standard and its adaptation to our design, show the manufacturing processes involved during the manufacture of the machine, illustrate the redesign or modification of the proposed design due to technical issues at the time of manufacture. The Charpy pendulum to be designed will serve as a testing machine for teaching purposes within the learning work of students studying engineering. The machine will be at the service of the people or industries that require it according to their interests. CAD software SolidWork has been used for the design of each of the components of the impact machine such as: the hammer, the turret, the jaws.